UNIVERSITY STUDENTS’ GROWTH GOALS, OPPORTUNITIES FOR GOAL FULFILLMENT, AND PERCEIVED UNIVERSITY AND MESOSYSTEM SUPPORT - Freibergs, Zigmunds; Kolesovs, Aleksandrs (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
This study assessed the relationship between students’ growth goals and perceived opportunities to achieve these goals in Latvia and the perceived support from the university and the mesosystem. Socialization models emphasize that the setting of personal goals occurs in continuous interaction with the sociocultural context, which includes perceived opportunities to achieve these goals and the interpersonal environment. Both – perceived support from close people (mesosystems) and perceived support from the university – are significant for students. The study involved 432 university students between 18 and 49. We have assessed the extent to which students’ goals regarding education, work, and personal growth are predicted by perceived opportunities to achieve these goals in Latvia and by the perceived support from parents, relatives, friends, classmates, teachers, and the university as an institution. The results of structural equation modeling revealed that personal growth goals are positively predicted by all three elements - the perceived opportunities to achieve these goals and the perceived academic and mesosystem support. The support of the classmates was connected to the support of the mesosystem that indicates the importance of friendly relations among students. Students’ growth goals were the most closely associated with the perceived support in their specific environment – the university. In general, the results confirm the complex interaction of personal growth goals with the social and cultural environment in particular circumstances.